Recurrent Pyogenic Granuloma: Surgical Management - Kavitha Parthasarathy; Nadarajah Vigneshwaran (Taylor & Francis Group, 2024)
Introduction Pyogenic granuloma is a relatively common tumor-like growth in the oral cavity, with a strong predilection for the gingiva. The preferred treatment for gingival pyogenic granuloma is conservative surgical excision, accompanied by meticulous scaling of adjacent teeth to remove potential irritants. However, this procedure can result in complications such as mucogingival defects, root exposure, and esthetic concerns, leading to additional functional and aesthetic challenges. This case report presents the surgical management of a patient with recurrent pyogenic granuloma associated with mucogingival defect.Case Presentation A 43-year-old Hispanic female was referred to our multidisciplinary faculty clinic at the University Texas School of Dentistry at Houston from a community dental clinic for evaluation and treatment of a gingival growth distal to tooth #11. The patient reported that the erythematous mass first appeared approximately three years ago during orthodontic treatment. The mass gradually increased in size, and the patient experienced bleeding and pain while brushing. After undergoing two excisional biopsies, the growth recurred rapidly within three weeks. However, a free gingival graft performed during the third surgery effectively prevented recurrence and increased the zone of attached gingiva at the site of tooth #11.Conclusion A free gingival graft procedure effectively prevents the recurrence of pyogenic granuloma while increasing the zone of attached gingiva. This enhancement improves overall periodontal health and stability, creating a more favorable environment for oral tissue.